2012
DOI: 10.1364/oe.20.008117
|View full text |Cite
|
Sign up to set email alerts
|

Dual-wavelength passive and hybrid mode-locking of 3, 45 and 10 GHz InAs/InP(100) quantum dot lasers

Abstract: Abstract:We present an investigation of passive and hybrid mode-locking in Fabry-Pérot type two-section InAs/InP(100) quantum dot lasers that show dual wavelength operation. Over the whole current and voltage range for mode-locking of these lasers, the optical output spectra show two distinct lobes. The two lobes provide a coherent bandwidth and are verified to lead to two synchronized optical pulses. The generated optical pulses are elongated in time due to a chirp which shows opposite signs over the two spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…It was found that not only mode-locking of both the mode groups was observed but also their pulses were synchronized. A similar mode-locking characteristic was also observed by Tahvili et al [142] in a dual-wavelength mode-locked laser, which corresponds to lasing emission from the same electronic transition of a 2×4000 µm 2 twosection device. In addition, employing a long 13 mm device (650 µm long SA), a stable mode locking of 3 GHz was also demonstrated which is the lowest repetition rate reported for a monolithic InAs/InP Qdots laser.…”
Section: Two Sectionsupporting
confidence: 81%
See 1 more Smart Citation
“…It was found that not only mode-locking of both the mode groups was observed but also their pulses were synchronized. A similar mode-locking characteristic was also observed by Tahvili et al [142] in a dual-wavelength mode-locked laser, which corresponds to lasing emission from the same electronic transition of a 2×4000 µm 2 twosection device. In addition, employing a long 13 mm device (650 µm long SA), a stable mode locking of 3 GHz was also demonstrated which is the lowest repetition rate reported for a monolithic InAs/InP Qdots laser.…”
Section: Two Sectionsupporting
confidence: 81%
“…Recently, hybrid mode-locking in two section InAs/InGaAsP/(100)-InP Qdots laser was investigated [142,143]. In this case an electrical modulation, with frequency close to the cavity freespectral range, is added to a reversely biased SA.…”
Section: Two Sectionmentioning
confidence: 99%
“…The principle of these measurements is similar to the one presented in [16]. In this method, the output signal from the PML was divided into two parts.…”
Section: Lettermentioning
confidence: 99%
“…Moreover, we examine the chirp of the output pulses by measurements of relative time delay between the spectral components of the comb [16].…”
mentioning
confidence: 99%
“…First is the performance of the MLLDs. Interesting performance has been achieved using quantum well 12 and quantum dot gain materials 13,14 . The semiconductor modelocked lasers are much more compact and in principle robust, but their overall performance is disappointing.…”
Section: Introductionmentioning
confidence: 99%